Pencak Silat Knockdown Anticipation Training Model for Student Athletes - Widiastuti, Widiastuti; Novian Saputro, Eko (Journal of Sport Science and Fitness, 2025)
Introduction: This study aims to improve the skills of anticipation of pull drops in pencak silat athletes in the competition category. The research was carried out from March to May 2025 at the Jakarta State University Sports Hall. The study was attended by DKI Jakarta student pencak silat athletes in the competition category. The lack of good knockdown anticipation techniques can result in injuries for athletes. Objectives: The dropping technique combined with a pull is regarded as highly effective for scoring points and securing victory in matches. Similarly, the fall anticipation technique using a pull is seen as a strategic approach to enhance an athlete’s ability to respond to falls. Based on this, implementing a training model focused on fall anticipation with pull is deemed suitable for improving athletes' preparedness. Mastery of these anticipation techniques not only contributes to performance but also plays a crucial role in reducing the risk of injury. Therefore, innovative solutions and updates are needed to address the challenges outlined, ensuring the training process operates at its highest potential. Method: The research methodology employed Research & Development approach using the ADDIE model, conducted at GOR UNJ, DKI Jakarta, during March-May 2025. The research subjects consisted of 30 pencak silat athletes PPLM DKI Jakarta in fight category. The instrument used is a test of pull fall anticipation skills that has been validated by pencak silat experts and experts. Based on the initial test data of the ability to anticipate dropping. Data analysis using SPSS to process the effectiveness results of the pre-test and post-test. Result: The research results demonstrated significant improvement from the pre-test average success rate of 3.1333 was obtained. Then after being given the material on the fall anticipation training model, the final test was carried out with an average success rate of 8.7333. There is an increase in the success rate.  Conclusion: The developed training model proved to be feasible and effective for enhancing skills anticipation of pull drops in pencak silat, providing valuable insight for martial arts training methodologies and competitive performance improvement.